Divine Mania: Alteration of Consciousness in Ancient Greece by Yulia Ustinova - Grosso, Michael (Journal of Scientific Exploration, 2021)
What role did altered states of consciousness play in the life of ancient Greek society? With consummate skill and scholarship, Yulia Ustinova answers this question in her book, Divine Mania: Alteration of Consciousness in Ancient Greece. It appears that the secret of the extraordinary creativity of the ancient Greeks was their receptivity to, and approval of, a particular altered state of consciousness they cultivated. Mania is the name for this but it must be qualified as “god-given.” Mania is a word that touches on a cluster of concepts: madness, ecstasy, and enthusiasm, engoddedness, to use Ustinova’s more vivid coinage. It seems a paradox that this special, strange and often quite frightening state of dissociation should be so closely linked to one of the most creative civilizations. Unlike the Roman and Egyptian, the Greek approved and recognized the value of god-inspired mania. Plato makes Socrates say in the Phaedrus that through mania we may obtain the “greatest blessings.” Whereas resistance to divine ecstasy can end in disaster, as Euripides illustrates in The Bacchants when Pentheus, a repressive authoritarian, tries to inhibit a posse of women from their ecstatic mountain dances. He is torn to shreds by his mother and her maniacal cohorts. This mindset of the ancient Greeks may have long ago petered out, but similar tendencies are constants, expressed in one form or another, throughout history.